2016
DOI: 10.7860/jcdr/2016/15276.7673
|View full text |Cite
|
Sign up to set email alerts
|

Brucellosis in Occupationally Exposed Groups

Abstract: Brucellosis most of the times was missed or misdiagnosed. Regular screenings for brucellosis and awareness programmes to increase KAP levels are necessary to control brucellosis in occupationally exposed groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
2
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 11 publications
2
38
2
3
Order By: Relevance
“…Among slaughterhouse personnel elsewhere, seroprevalence estimates of 59% (44/75) in Iran [118], 22% (78/360) in Pakistan [119] and as high as 39% (66/170) in Nigeria [120] have been documented. In India, 3.8% (42/1086) in veterinarians and 15% (8/186) in abattoir personnel have been recorded [121]. Differences across countries could be attributed to prevalence differences in animals.…”
Section: Resultsmentioning
confidence: 99%
“…Among slaughterhouse personnel elsewhere, seroprevalence estimates of 59% (44/75) in Iran [118], 22% (78/360) in Pakistan [119] and as high as 39% (66/170) in Nigeria [120] have been documented. In India, 3.8% (42/1086) in veterinarians and 15% (8/186) in abattoir personnel have been recorded [121]. Differences across countries could be attributed to prevalence differences in animals.…”
Section: Resultsmentioning
confidence: 99%
“…In a study by Haddadi et al in Tehran, 17.1% of patients had occupational exposure to livestock (13). In other studies, occupational exposure has been reported in 58.7%, 71%, 27%, and 32% of cases (7,14). Therefore, although occupation is considered a risk factor, the disease is not necessarily transmitted occupationally in developing countries.…”
Section: Discussionmentioning
confidence: 90%
“…Esta situación representa un serio riesgo para la salud pública, ya que el consumo de leche y quesos sin pasteurizar, procedentes de rebaños afectados por brucelosis, constituye uno de los mecanismos fundamentales de transmisión de la enfermedad a los humanos ( Un aspecto primordial para el control de la brucelosis en personas que se encuentra en el grupo de alto riesgo de padecer la enfermedad es la evaluación serológica periódica (Mangalgi et al, 2016). Sin embargo, en este estudio se comprobó que no se investiga periódicamente al personal que labora en estos centros procesadores; por tanto, se incumple lo establecido en las buenas prácti-cas ganaderas con relación a la protección del personal (FAO y FIL, 2012).…”
Section: Discussionunclassified